2017
DOI: 10.18632/oncotarget.18530
|View full text |Cite
|
Sign up to set email alerts
|

Gamma analysis with a gamma criterion of 2%/1 mm for stereotactic ablative radiotherapy delivered with volumetric modulated arc therapy technique: a single institution experience

Abstract: To report a single-institution experience of gamma evaluations with 2%/1 mm for stereotactic ablative radiotherapy (SABR) delivered with volumetric modulated arc therapy (VMAT) technique, from January 2014 to January 2016. A total of 168 SABR VMAT plans were analyzed with a gamma criterion of 2%/1 mm, a threshold value of 10%, and a tolerance level of 90%. Of the 168 cases, four cases failed with 2%/1 mm. The average passing rate was 97.0% ± 2.5%. Three of the four failed cases showed passing rates higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…This presented a challenge, because historically the Gamma Knife has been considered capable of delivering dose distributions accurately without the necessity of patient‐specific measurements. A number of reports have described PSQA for linac‐based SRS and SBRT . In general, these articles described results similar to those we achieved with our PSQA program.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This presented a challenge, because historically the Gamma Knife has been considered capable of delivering dose distributions accurately without the necessity of patient‐specific measurements. A number of reports have described PSQA for linac‐based SRS and SBRT . In general, these articles described results similar to those we achieved with our PSQA program.…”
Section: Discussionsupporting
confidence: 73%
“…Wen et al using a 3%/1 mm gamma criteria achieved an overall pass rate of 95% for linac‐based SRS/SBRT. Kim et al achieved an average gamma of 97.0 ± 2.5% for stereotactic ablative radiotherapy/volumetric‐modulated arc therapy (VMAT) with 2%/1‐mm criteria. Colodro et al achieved an average gamma pass rate of 92.7 ± 2.9% with 3%/1.5‐mm gamma criteria for VMAT SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2% /2 mm criterion remains widely used in clinical practice [ 35 , 36 ], no clear international guidelines exist. In the special setting of stereotactic ablative RT delivered by VMAT, a 2D global gamma analysis with a 2%/1 mm criterion provided promising results [ 37 ]. Comparison between such criteria and our workflow seemed to be of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that more stringent criteria (e.g., 2%/1 mm) may be useful for stereotactic radiotherapy owing to a higher sensitivity in the detection of delivery errors. Therefore, our model requires improvement to increase the MAE prediction accuracy in this range 25,26 …”
Section: Discussionmentioning
confidence: 99%